Gaps and benefits of fiscal rule adopted by the 617 Law of 2000 (2016)
Law 617 enacted in 2000, is regarded as one of the key instruments in the implementation of policies of fiscal control in Colombia, like most of the country's standards, this has been caused by particular situations and emerged with the purpose of meeting essentially excessive levels of operating expenses in the territorial level by the absence of limits in this regard and at the national level by creating a significant number of municipalities during the years 1995-1999, circumstances requiring special attention from the government national, but that inconsistency in setting scales of categorization and lack of foresight, the law passed was effective in immediate control, but requires a major overhaul, because it did not foresee the treatment of conditions currently present municipalities and departments from the country.